The role of Filipino masculine ideology on the adaptive coping, psychological wellbeing and vicarious trauma of first responders - Agbayani, Bianca Eloise M (Archīum Ateneo, 2019)
The exposure of first responders to emergencies and disaster puts them at high risk of experiencing vicarious trauma. First responders are typically male and literature suggests that a negative connotation of masculinity creates a stigma that leads to low help-seeking behaviour and poorer psychological outcomes. This study examines Filipino dimensions of masculinity namely perceived cognitive ability, sense of community, and assertive dominance and how these dimensions predict adaptive coping and its outcomes. Surveys of 135 male first responders reveal that perceived cognitive ability and sense of community positively predict adaptive coping. Results also support the hypothesis that adaptive coping mediates the relationship of perceived cognitive ability, and sense of community positively with psychological well-being. However, there was no relationship between assertive dominance and adaptive coping. Rather, assertive dominance predicted vicarious trauma. The results contribute to the literature by showing that masculinity ideologies have both positive and negative relationships with mental health. This has implications on how emergency organizations can help support first responders.